2015
DOI: 10.1590/0037-8682-0174-2014
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium spp., Giardia spp. and other pathogenic intestinal parasites in the Beberibe River in the State of Pernambuco, Brazil

Abstract: Introduction: Transmission of pathogenic protozoa and helminths by water is a serious public health problem. In this study, we analyzed the presence of these organisms in the Beberibe River in Pernambuco, Brazil. Methods: Parasite analysis was performed using the Hoffman, Pons, & Janer method followed by centrifugation and preparation of slides by staining with acetic acid and Lugol's solution. Protozoan oocysts were isolated by the modifi ed Ziehl Neelsen method. Results: Cryptosporidium spp., Giardia spp. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Very few studies were conducted in other regions, likely reflecting the social disparities existing throughout the country. Two studies [ 27 , 28 ] were conducted in Pernambuco (a state in the Northeast region). The first study found a prevalence of 50.0% for Giardia cysts in samples from the Beberibe River which suffers anthropogenic and animal contamination as demonstrated by high levels of E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies were conducted in other regions, likely reflecting the social disparities existing throughout the country. Two studies [ 27 , 28 ] were conducted in Pernambuco (a state in the Northeast region). The first study found a prevalence of 50.0% for Giardia cysts in samples from the Beberibe River which suffers anthropogenic and animal contamination as demonstrated by high levels of E .…”
Section: Resultsmentioning
confidence: 99%
“…The first study found a prevalence of 50.0% for Giardia cysts in samples from the Beberibe River which suffers anthropogenic and animal contamination as demonstrated by high levels of E . coli found in its water (from 50,000 to ≥ 160,000 NMP/100mL) [ 27 ]. The second study investigated bacterial and parasite contamination of rainwater stored in tanks and clay pots, in a semi-arid region of Northeast Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of C. parvum oocysts in water is also ubiquitous in surface water (An et al., 2011; Bautista et al., 2018; Chuah et al., 2016; Damiani et al., 2013; de Freitas et al., 2015; Imre et al., 2017; L. Ma et al., 2019; Stokdyk et al., 2019; Vermeulen et al., 2019), groundwater (Bridgman et al., 1995; Chique et al., 2020; Damiani et al., 2013; Daniels et al., 2018; Hancock et al., 1998; Lee & Murphy, 2020; Moulton‐Hancock et al., 2000; Stokdyk et al., 2019), wastewater (Castro‐Hermida et al., 2008; Hamilton et al., 2018; Kitajima et al., 2014), irrigation water (Chaidez et al., 2005; Khashiboun et al., 2007; Sampson et al., 2017; Spanakos et al., 2015), and runoff (Atwill et al., 2006; Cizek et al., 2008; Davidson et al., 2014; Kaucner et al., 2005; Lu et al., 2016; Miller et al., 2008; Sterk et al., 2016; Swaffer et al., 2014). Studies investigating the occurrence of C. parvum oocysts in environmental compartments established their presence in soil (Balderrama‐Carmona et al., 2014; Barwick et al., 2003; Boyer & Kuczynska, 2010; Hong et al., 2014; Zopp et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sites F3, F4 and F5 are located in an area of dense urbanization and receive a signi cant load of domestic sewage, which results in a considerable increase in the level of pollution in this river (Veras et al, 2016;Veras et al, 2019), aggravated by the direct disposal of waste from small industries in its surroundings. Previous studies have detected the presence of intestinal parasites (mainly protozoa and helminths) (Freitas et al, 2015) and pharmaceutical products (diclofenac and paracetamol) (Veras et al, 2019) in water samples from the Beberibe River, indicating it is the direct destination of untreated domestic waste in the river. Although the Beberibe River is considered one of the most polluted rivers in the region, it supplies water to about 100,000 people (Freitas et al, 2015).…”
Section: Resultsmentioning
confidence: 99%